We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
182
1
avatar

The quadratic -6x^2+36x+216 can be written in the form a(x+b)^2+c, where a, b, and c are constants. What is a+b+c?

 Jun 26, 2018

Best Answer 

 #1
avatar+22343 
+1

The quadratic -6x^2+36x+216 can be written in the form a(x+b)^2+c,

where a, b, and c are constants.

What is a+b+c?

 

\(\begin{array}{|rcll|} \hline && -6x^2+36x+216 \\ &=& -6(x^2-6x) + 216 \\ &=& -6[ (x-3)^2 -9 ] +216 \\ &=& -6(x-3)^2 + 6\cdot 9 + 216 \\ &=& -6(x-3)^2 +54 + 216 \\ &=& -6(x-3)^2 + 270 \quad & | \quad \text{compare with $a(x+b)^2+c$} \\\\ a &=& -6 \\ b &=& -3 \\ c &=& 270 \\ a+b+c &=& -6-3+270 \\ \mathbf{a+b+c} & \mathbf{=}&\mathbf{ 261 } \\ \hline \end{array}\)

 

laugh

 Jun 26, 2018
 #1
avatar+22343 
+1
Best Answer

The quadratic -6x^2+36x+216 can be written in the form a(x+b)^2+c,

where a, b, and c are constants.

What is a+b+c?

 

\(\begin{array}{|rcll|} \hline && -6x^2+36x+216 \\ &=& -6(x^2-6x) + 216 \\ &=& -6[ (x-3)^2 -9 ] +216 \\ &=& -6(x-3)^2 + 6\cdot 9 + 216 \\ &=& -6(x-3)^2 +54 + 216 \\ &=& -6(x-3)^2 + 270 \quad & | \quad \text{compare with $a(x+b)^2+c$} \\\\ a &=& -6 \\ b &=& -3 \\ c &=& 270 \\ a+b+c &=& -6-3+270 \\ \mathbf{a+b+c} & \mathbf{=}&\mathbf{ 261 } \\ \hline \end{array}\)

 

laugh

heureka Jun 26, 2018

24 Online Users

avatar
avatar
avatar